CRITICAL ANALYSIS OF LABORATORY SERVICES IN EMERGENCY MEDICINE IN EVALUATING TEST UTILIZATION, TURNAROUND TIME, AND IMPACT ON CLINICAL DECISION-MAKING IN CRITICAL CARE SCENARIOS. - Mansour Ali Gassem Al Sari, MubarkMohmmad Seed Alqufayli, Bader Saleh Mesfer Al Quraish, Hadi Saleh Hadi Almahmeed, Alhassan Saleh Hadi Almuhamidh, Ali Saleh Mohammed Al Garea, Ali Muhsin Ali Al Ishaq, Hamad Abdullah Mobarak Balharith, (Chelonian Research Foundation, 2022)
Lab services are one of the key elements of emergency medicine because they deliver analysis data to facilitate critical decisions taken in severe cases. This paper critically analyzes the role of laboratory services in emergency medicine, particularly in terms of test utilization, test turnaround time, and their demands on practitioners regarding diagnosis. This study is based on in-depth literature reviews, empirical data analytics, and analysis of laboratory services. In the practice of the current period, problems and opportunities for advancement are exposed. With the emerging results, laboratory tests have developed the necessity of optimizing test usage, minimizing turnaround time, and combining the test with clinical workflow for higher clinical utility. Keywords: laboratory, emergency care administration, proper test paper use, turnaround time, clinical decisions.